THE NOTION OF LINGUOCULTUREME AND ITS TYPES (American Journal of Research in Humanities and Social Sciences, 2023)
Linguoculturology, or cultural linguistics, just like any other scientific discipline, has its own terminology and a variety of aspects and trends. This article explores various trends of cultural linguistics and main notions of linguoculturology. However, the article mainly focuses on the definitions of linguocultureme as a basic unit of linguoculturology suggested by various researchers.